Financial value and public relations - TOSUN, NURHAN ZEYNEP (My University, 2004)
From a theoretical perspective, there is an emergent trend toward the planning of financial public relations strategies in order to add financial value to businesses. However, the benefits of strategising and planning cannot be fully realised unless they are supported by the entire range of corporate communications activities. In this paper, we explore the idea that to create financial value in business there should be a synergistic interaction among all public relations activities, here exemplified through an embryonic process model. © 2004, Emerald Group Publishing Limited
Keywords: Asset valuation; Organizations; Public relations